Mindfulness Training for Improving Attention Regulation in University Students: Is It Effective? and Do Yoga and Homework Matter? - Wimmer, Lena; Bellingrath, Silja; von Stockhausen, Lisa (Frontiers in Psychology, 2020)
The present study examined effects of mindfulness training on attention regulation in university students, and whether the potential benefits of implementation are influenced by the yoga component of mindfulness-based interventions (MBIs) and/or by homework practice. In a non-randomized trial with pre- and post-assessments, n=180 university students were allocated to either mindfulness training (experimental groups), awareness activities (active control group), or no training (passive control group). Mindfulness was taught in two MBIs, one of which including yoga, the other excluding yoga. Attention regulation was operationalized via behavioral indicators, namely sustained attention, cognitive flexibility, cognitive inhibition, and data-driven information processing. With the exception of speed in a cognitive flexibility task, results indicated no systematic or differential advantage of mindfulness training, with or without yoga, regarding the aspects of attention regulation. There was no consistent influence of homework quantity or quality. Implications for mindfulness training in academic contexts are discussed.